DETEKSI DINI DISLIPIDEMIA PADA TENAGA PENDIDIK SEKOLAH DASAR - Irawaty, Enny; Ardin, Muhammad Ajib; Yosafat, Fernando (Jurnal Serina Abdimas, 2024)
Dyslipidemia is a lipid imbalance such as cholesterol, low-density lipoprotein cholesterol (LDL-C), triglycerides, and high-density lipoprotein (HDL). This condition can be caused by diet, tobacco exposure, or genetics and can lead to cardiovascular disease with severe complications. High cholesterol levels often have no symptoms, so most people do not realize that their cholesterol is too high, and they rarely carry out early detection. The survey showed that our clients, primary school teachers, rarely do cholesterol tests. They often consume foods that contain cholesterol and are physically inactive due to their busy daily activities. Based on client problems, the community service team of FK UNTAR intends to check blood cholesterol levels. The aim of this PKM activity is to increase awareness of the importance of blood cholesterol level checking and increase insight regarding how to maintain cholesterol levels in the body in a normal condition. A total of 23 participants took part in this activity. The results showed that 26.1% of participants had high total cholesterol levels, 34.8% of participants had LDL cholesterol levels close to optimal and borderline, 8.7% of participants had low HDL cholesterol levels, 82.6% of participants had normal triglyceride levels, and 21.7% of participants experienced dyslipidemia. The results of this activity showed that participants with dyslipidemia were quite high. It is hoped that this activity can increase participants' awareness so that they can monitor or carry out regular cholesterol checks in an effort to prevent the emergence of metabolic disease disorders in the future.